COMBINING ABILITY ANALYSIS FOR SEED COTTON YIELD, SOME OF ITS COMPONENTS AND RELATIVE SUSCEPTIBILITYITY FOR BOLL WORM INFESTATION - K. M. Dawod; S. I. Abdullah; M. I. Mohammad (Mesopotamia Journal of Agriculture)
Upland cotton varieties and lines viz. Coker310, SP8886, Lachata, Montana, Halab33, AC22, Gourd26, Iranean16, Syrian line S230 and Chrip-AM539 and their half diallel crosses were planted at two locations, the first at College of Agriculture and Forestry, Mosul University in April, 19, 2010 and the second at Al-Hawija, Kirkuk Governorate in April, 20, 2010 using randomized complete block design with three replications. Combining analysis of the two locations data carried out and variances and effects of general and specific combining abilities were estimated for characters: plant height, number of fruiting branches, number of bolls per plant, boll weight, seed index, lint index, relative sensitivity to boll worm infestation and seed cotton yield per plant. The results showed that location mean square was significant at 1% level for number of bolls per plant and relative sensitivity to boll worm infestation, and at 5% level for seed cotton yield per plant, while mean square of genotypes, general and specific combining abilities and their interactions with locations were highly significant for all characters. The variety SP8886 appeared as good general combiner for five characters including seed cotton yield and relative sensitivity to boll worm infestation, followed by varieties Halab33 and Iranean16 and Syrian line S230. The hybrid (SP8886 x Iranean16) was good specific combiner for six characters including seed cotton yield and relative sensitivity to boll worm infestation, that is useful to use these genotypes in future breeding programmes.